BIODIESEL DARI MINYAK JARAK PAGAR DENGAN VARIASI PENAMBAHAN CO-SOLVENT DAN WAKTU REAKSI - Elvianto Dwi Daryono, M.Istnaeny Hudha, Muyassaroh (Jurnal Teknik Kimia, 2012)
Transesterification reaction in biodiesel manufacturing process is slow because it takes place in a two-phase system.  This problem can be overcome by adding a co-solvent that is not reactive. The addition of co-solvent aims to form a single phase system. Therefore, this study is conducted with the aim  of understanding the effect of adding co-solvent of methyl ester Tetra Hydro Furan (THF) produced in the transesterification reaction of biodiesel from Jatropha curcas oil (Jatropha oil). The variables studied were the number of THF and reaction time. In addition, transesterification reactions are also carried out without the addition of co-solvent (conventional method) for comparison. The reaction temperature is maintained at 300C and atmospheric pressure. The results showed that transesterification reaction with the addition of co-solvent is 2-10 minutes faster than the conventional reaction. Transesterification reaction with the addition of co-solvent produces higher methyl ester amount than conventional methods. 94.79% methyl ester amount is achieved when the mass ratio of THF:Methanol = 2:1, molar ratio of Jatropha oil: Methanol = 1:6 and 1.3% NaOH catalyst-weight. Keywords: biodiesel, co-solvent, Jatropha oil, transesterification